2010
DOI: 10.1177/0009922809352679
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Board Review Course for Residents “at Risk”

Abstract: Pediatric residents at risk for not passing their Pediatric board certification exams benefited from a board review course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…Some prior work in other specialties has shown that directed study can influence in-training exam performance and board pass rates 46. To our knowledge, no previously published studies in EM have shown any specific exam preparation technique to be superior.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Some prior work in other specialties has shown that directed study can influence in-training exam performance and board pass rates 46. To our knowledge, no previously published studies in EM have shown any specific exam preparation technique to be superior.…”
Section: Discussionmentioning
confidence: 79%
“…The best method of preparation for in-training exams is currently unclear, and programs to aid in preparation have reported mixed results 26. Cheng found that an EM residency-developed review course did not affect performance on the in-training exam 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are at odds with those of a number of studies that have evaluated performance on written or clinical examinations before and after a specific remediation intervention 7,14–38 and concluded that the intervention was effective. However, single studies ‘are limited in the generalisability of the knowledge they produce about concepts, populations, settings and times’ and ‘frequently illuminate only one part of a larger explanatory puzzle’ 39 .…”
Section: Introductionmentioning
confidence: 66%
“…But, the large majority of residents are presumably doing well enough. Since more than 95 % of those entering post-graduate medical training programs graduate without being terminated [26], senior educators might consider shifting from "universal screening" (a TSA model) to "risk based regulation" (in which "at risk" trainees are quickly spotted and become the primary focus for supervisory intervention) as a better way to invest resources [27]. Many on the front lines question the value of expending considerable resource on these seemingly excessive efforts devoted to the large majority who are doing at least "good enough" work, and for whom no data exists to show that micro-attention to competencies (or feeding central authorities mounds of micro-documentation for intermediate evaluations) offers any added value above "training as usual."…”
Section: To Address Assessment Issuesmentioning
confidence: 99%